Il “diritto di nominazione”. Un nuovo diritto per i bambini e le bambine nelle scuole italiane - Emiliano Macinai; Marianna Piccioli (Studi sulla Formazione)
The main topics of this article were discussed in the “Congreso Internacional de Educación y Diversidad” held in April 2025 at the Universidad de Zaragoza, in Spain. During the conference, we were invited to give a speech on El derecho de nomination. Un nuevo derecho de los niños y las niñas en las escuelas italianas. Here, we resume and develop that report, examining in depth in the first part, written by Emiliano Macinai, the theoretical assumptions and the framework that forms the background to the topic; and in the second part, written by Marianna Piccioli, the analysis of the results of a research conducted in the previous months.